Reconstruction of Porcine Critical-Sized Mandibular Defects with Free Fibular Flaps: The Development of a Craniomaxillofacial Surgery Model - Dorafshar, Amir H.; Mohan, Raja; Mundinger, Gerhard S.; Brown, Emile N.; Kelamis, Alex J.; Bojovic, Branko; Christy, Michael R.; Rodriguez, Eduardo D. (Journal of Reconstructive Microsurgery, 2014)
Vascularized bone flaps are the well-known standards of care for reconstruction of segmental mandibular defects ≥ 6 cm. We developed a large animal critical-sized mandibular defect model in which osseous free fibula flaps were used for reconstruction.In this study a total of eight 3-month-old Yorkshire pigs underwent 6 cm full-thickness resection of the left hemimandible. An osseous free fibula flap from the left leg was harvested and contoured to the mandibular defect. Bone placement and plate position was confirmed with fluoroscopy. Animals were followed with serial radiographs and clinical evaluations.Free fibulas were transferred successfully in all eight animals. The average operative time was 346 minutes, and the average flap ischemia time was 86 minutes. The average volume ratio of reconstructed hemimandibles to nonoperated control hemimandibles was 0.72 ± 0.33. The average maximum fracture load was 689 ± 262 N, and the average ratio of biomechanical fracture load for these samples compared with contralateral control hemimandibles was 0.88 ± 0.25.It is concluded that the porcine osseous free fibula flaps can be reliably harvested and viably transferred to critical-sized posterior mandibular defects with acceptable long-term results. The described microsurgical large animal model is acceptable for use in craniomaxillofacial experimentation.
Keywords: free fibula flap; mandibular reconstruction; microsurgery